2016
DOI: 10.4137/jen.s25100
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model to Study Tau Pathology

Abstract: Tau proteins play a role in the stabilization of microtubules, but in pathological conditions, tauopathies, tau is modified by phosphorylation and can aggregate into aberrant aggregates. These aggregates could be toxic to cells, and different cell models have been used to test for compounds that might prevent these tau modifications. Here, we have used a cell model involving the overexpression of human tau in human embryonic kidney 293 cells. In human embryonic kidney 293 cells expressing tau in a stable manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…We were unable to determine Φ values for AT100, due to lack of binding to tau expressed in HEK293FT cells. Endogenous kinases in HEK293FT cells phosphorylate human tau (Camero et al 2014;Houck et al 2016). We showed that co-transfection of tau with GSK-3β led to increased phosphorylation of tau, but not for the AT100 target site (Thr212/Ser214).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We were unable to determine Φ values for AT100, due to lack of binding to tau expressed in HEK293FT cells. Endogenous kinases in HEK293FT cells phosphorylate human tau (Camero et al 2014;Houck et al 2016). We showed that co-transfection of tau with GSK-3β led to increased phosphorylation of tau, but not for the AT100 target site (Thr212/Ser214).…”
Section: Discussionmentioning
confidence: 85%
“…Previous reports indicated that endogenous tau expression is undetected in HEK293 cells (Kfoury et al 2012;Liu et al 2013). In addition, when transfected with human tau, endogenous kinases in HEK293FT cells phosphorylated human tau (Camero et al 2014;Houck et al 2016). Leveraging these facts, we developed a ratiometric assay to quantify the specificity of phospho-tau antibodies (Fig.…”
Section: Phi: a Generalizable Parameter For Measuring The Specificitymentioning
confidence: 99%
“…Tauopathy is initiated by forming neurofibrillary tangles, neuritic plaques, and neuropil threads [40]. Excessive phosphorylation of tau has also been shown to contribute to tangle formation [41] and prevents neuronal cell function. In AD, brain synapses are disrupted by the Aβ plaques and tau tangles, damaged neurons die.…”
Section: Pathophysiologymentioning
confidence: 99%
“…We demonstrated that circAβ-a serves as a template for the synthesis of a novel Aβ-containing polypeptide variant. Notably, the resulting product is further processed into Aβ peptides in human embryonic kidney 293 (HEK293) cells, which represents a well-established cellular model in AD research [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%